Photoluminescence and structural analysis of trivalent europium doped MLaAl3O7 (M = Ba, Ca, Mg and Sr) nanophosphors. (21st January 2020) - Kadyan, Sonika; Singh, Kuldeep; Singh, Sitender; Sheoran, Suman; Singh, Jasbir; Singh, Devender
Abstract: The solution combustion technique was used to synthesize MLaAl3 O7 (M = Ba, Ca, Mg, and Sr) nanophosphors‐doped with Eu 3+ using metal nitrates as precursors. The photoluminescence (PL) emission spectra exhibited three peaks at 587–591, 610–616, and 653–654 corresponding to 5 D0 → 7 F1, 5 D0 → 7 F2, and 5 D0 → 7 F3 transitions, respectively. Upon excitation at 254 nm, these nanophosphors displayed strong red emission with the dominant peak attributed to the 5 D0 → 7 F2 transition of Eu 3+ . The materials were further heated at 900 and 1050°C for 2 h to examine the consequence of temperature on crystal lattice and PL emission intensity. X‐ray diffraction (XRD) analysis proved that all the synthesized materials were of a crystalline nature. CaLaAl3 O7 material has a tetragonal crystal structure with space group P421m. Scherer's equation was used to calculate the crystallite size of synthesized phosphors using XRD data. A Fourier transformation infrared study was used to observe the stretching vibrations of metal–oxygen bonds. Infrared peaks for stretching vibrations corresponding to lanthanum–oxygen and aluminium–oxygen bonds were found at 582 and 777 cm –1 respectively for CaLaAl3 O7 phosphor material. Transmission electron microscopy images were used to determine the size of particles (18–37 nm for the as‐prepared materials) and also to analyze the three‐dimensional view of these materials. The experimental data indicate that these materials may be promising red‐emitting nanophosphors for use in white light‐emitting diodes.